The ratio analysis of the banking industry in Hong Kong - Wang, Xueying (2019)
The purpose of this paper is to explore the influences of different ratios of bank, namely, internal factors and macroeconomic determinants of bank performance in Hong Kong banking sector during the period from 2013 to 2018. This paper selects 21 banks, using the panel data imbalance of the Hong Kong banking industry, and adopts a fixed effect model to capture the unobservable heterogeneity of banks. Two performance measurements, ROAA and ROAE are used in this paper to capture the differences in the determinants of Hong Kong banking industry. To be specific, cost to income, equity to total assets, net loans to total assets, loan loss reserves to gross loans, net interest margin and bank size (total assets) are selected as internal variables to represents asset quality, liquidity, credit risk, operating efficiency and capital adequacy of the banks. Turning to the external factors, GDP growth rate and inflation rate are used in this paper. The estimation results indicate that there are few differences in performance measure under the conditions that whether external factors are involved. Also, the empirical results illustrate that external variable inflation rate is significant and positive for ROAE while insignificant for ROAA, which indicates that the impact of inflation on shareholder is greater and more significant than the impact on bank assets.